2002
DOI: 10.4315/0362-028x-65.12.1881
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Cucumber Fruit through Adhesion

Abstract: In this study, the adhesion of bacteria to fresh cucumber surfaces in aqueous suspension was shown to be dependent on time of incubation, inoculum species and concentration, and temperature. The adhesion of bacteria to the fruit in wash water was less extensive at lower temperatures and shorter exposure times. Various species of bacteria were adsorbed to cucumber surfaces in the following relative order: Salmonella Typhimurium > Staphylococcus aureus > Lactobacillus plantarum > Listeria monocytogenes. Cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 31 publications
3
21
0
1
Order By: Relevance
“…Internalization of Salmonella spp. has also been reported in mangoes (Penteado et al 2004), tomatoes (Buchanan et al 1999), apple (Zhuang et al 1995), lettuce (Reina et al 2002), and sweet basil (Gorbatsevich et al 2013). Internalization may occur naturally as reported in these studies, or may occur during washing (due to immersion) at post-harvest stages (Gomez-Lopez et al 2013).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Internalization of Salmonella spp. has also been reported in mangoes (Penteado et al 2004), tomatoes (Buchanan et al 1999), apple (Zhuang et al 1995), lettuce (Reina et al 2002), and sweet basil (Gorbatsevich et al 2013). Internalization may occur naturally as reported in these studies, or may occur during washing (due to immersion) at post-harvest stages (Gomez-Lopez et al 2013).…”
Section: Discussionmentioning
confidence: 59%
“…Some studies reported that bacterial strains varied widely in their endophytic colonization abilities, which could be related to the plant defense mechanisms that targeted bacterial extracellular components (Dong et al 2003;Iniguez et al 2005). Water used for the washing of the fruits can be contaminated by the pathogens while acting as the source of the internalization of the pathogens through the lenticels, stomata and the injured parts (Reina et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal cells close to the stomata were elevated and covered with a smooth wax layer. Marked epidermal cells were less observed than those by Reina et al (2002), because they used fixation and critical point drying with CO 2 .…”
Section: Fungos Necrotróficos Associados à Microfissura Epidérmica Camentioning
confidence: 95%
“…Chilling injury was more severe in fruits stored during 23 days, and B. cinerea developed during the first day of shelf life at 20 o C (Figure 2 G and H). Sometimes, unidentified coccus-bacterium of 2-3 µm Ø were also located close (or not) to some stomata, probably a typical microbial community on fruit surface (Reina et al, 2002).…”
Section: Fungos Necrotróficos Associados à Microfissura Epidérmica Camentioning
confidence: 99%
“…12) The wax layer of vegetable surfaces inhibits the penetration of NaClO into plant tissues and affects the numbers of adsorbed bacteria. 18) When bacteria form biofilms, they are not easily killed by disinfectants such as NaClO, 19,20) but it takes several days to produce biofilms. The physical structure of vegetables is pointed out as another important factor in disinfection of bacteria.…”
mentioning
confidence: 99%